Silica Fume and Microwave Incinerated Rice Husk Ash (MIRHA) as a Multiple Binder in Concrete - Ahmad Farhan Bin Jopri, Ahmad Farhan (Universiti Teknologi Petronas, 2009)
Concrete is a construction material composed of cement as well as other cementitious materials such as fly ash and slag cement, aggregate, sand, water, and chemical admixtures. The word concrete comes from the Latin word "concretus". which means "hardened" or "hard". Concrete can be designed to withstand the harshest environments while taking on the most inspirational forms. Engineers are continuously pushing the limits with the help of innovative chemical admixtures and supplementary cernentitious materials often incorporated in the concrete mix to reduce cement contents, improve workability, increase strength and enhance durability. There are many types of admixtures being used in concrete. Strict air-pollution controls and regulations have produced an abundance of industrial byproducts that can be used as admixtures such as silica fume and rice husk ash. The use of such byproducts in concrete construction not only enhances the properties of concrete, but it also reduces cost, keep environment clean, and can avoid the byproducts form being land-filled. Furthermore, admixtures can replace a portion of the cement content and it will greatly reduce the cost especially for mass amount of concrete